INCONSISTENCY OF AIR QUALITY LEVEL DURING SEVERAL PHASES OF COVID-19 MOVEMENT RESTRICTIONS IN MALAYSIA - ABDULLAH S.; ROZALI N.H.S.C.; MANSOR A.A.; AHMAD A.N.; AHMED A.N.; DOM N.C.; ZULKIFLI M.F.R.; JUSOH S.M.; MANSOR W.N.W.; ISMAIL M. (Universiti Malaysia Terengganu, 2024)
Analysing the air quality during the Covid-19 pandemic is important to evaluate for air quality management strategies and plans. This study aims to assess the air quality changes during Movement Control Order (MCO) in Malaysia by investigating air pollutants trends and evaluating the relative changes of air pollutants during different Movement Control Order (MCO) phases. Data from 18 March 2020 to 30 June 2020 was acquired which comprised of Sulphur Dioxide (SO2), Carbon Monoxide (CO), Nitrogen Dioxide (NO2), Ozone (O3), and Particulate Matter (PM2.5, PM10) this was checked on an hourly basis at65 stations in Malaysia. The data were retrieved from the Department of Environment (DOE). The trend of air pollutants for all parameters decreased during the restricted lockdown phases and increased during unrestricted lockdown phases. During strict lockdown the average relative changes for the highest percentage reduction of PM10, PM2.5, SO2, NO2, O3, and CO were 61.5%, 63.2%, 51.9%, 35.0%, 66.9%, and 47.3% while highest percentage reduction during unrestricted lockdown with value 23.1%, 29.3%, 38.7%, 9.1%, 56.6%, and 29.4%. In conclusion, there are variations in the levels of criteria pollutants during the different MCO's in Malaysia due to the Covid-19 pandemic. (2023) UMT Press.